2016
DOI: 10.1080/10538712.2015.1119773
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Posttraumatic Growth in Adult Survivors of Child Sexual Abuse

Abstract: Potential negative sequelae for survivors of child sexual abuse is well documented. However, growing evidence suggests that some individuals who actively cope with traumatic events can progress from a negative trajectory toward positive psychological change, often termed posttraumatic growth. Current posttraumatic growth theories may be of limited applicability to developmental considerations involved in child sexual abuse. This explorative study examines posttraumatic growth among adult female survivors of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
2
33
0
9
Order By: Relevance
“…Qualitative studies also found reduced shame through: increased self‐compassion (Hartley, Johnco, Hofmeyr, & Berry, ; Saha et al, ); connecting with others or engagement in helping others (Arias & Johnson, ; Dorahy & Clearwater, ; Saha et al, ); disclosing and externalising shame and blame; and through learning about abuse dynamics (Arias & Johnson, ; Chouliara et al, ). The findings from these studies support shame‐based and compassion‐based interventions as important to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies also found reduced shame through: increased self‐compassion (Hartley, Johnco, Hofmeyr, & Berry, ; Saha et al, ); connecting with others or engagement in helping others (Arias & Johnson, ; Dorahy & Clearwater, ; Saha et al, ); disclosing and externalising shame and blame; and through learning about abuse dynamics (Arias & Johnson, ; Chouliara et al, ). The findings from these studies support shame‐based and compassion‐based interventions as important to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal/thoracic injuries (Kotch et al 1993) Acquire brain injuries (Buchweitz et al 2019) Bruises, welts, lacerations, and abrasions (Alexander et al 2001) Fractures (Felitti 1998) Eyes injuries (McBeth et al 1999) Sexual and reproductive ill-health Reproductive health problems (Cooperman and Merten 2001) Sexual dysfunction (Rapsey et al 2019) Sexually transmitted diseases, including HIV/AIDS (Shamu et al 2019) Unwanted pregnancy (Hall et al 2019) Cognitive, emotional and behavioral disorders Developmental delays (Croft et al 2019) Alcohol and drug abuse (Cicchetti and Handley 2019) Cognitive impairment (Aas et al 2019) Delinquent, violent and other risk-taking behaviors (Mumford et al 2019) Depression and anxiety (Rapsey et al 2019) Deliberate food restriction and body-image problem (Bahji et al 2019) Feelings of shame and guilt (Baiden et al 2019) Poor self-esteem (McDonald et al 2019) Post-traumatic stress disorder (Hartley et al 2016) Deliberate self-harm and Suicidal behavior (Shapero et al 2019) Other longer-term health consequences Cancer (Henchoz et al 2019) Respiratory diseases (Riedl et al 2019) Fibromyalgia (Varinen et al 2019) Irritable bowel syndrome (Parker et al 2019) Ischemic heart disease (Obi et al 2019) Reproductive health problems such as infertility (Panisch 2019) Child maltreatment tends to trigger a myriad of physical, sexual and reproductive problems in addition to cognitive, emotional and behavioral disorders as shown in Table 2. It might also be advisable for those working in the caregiving profession to be trained in the biopsychosocial approach.…”
Section: Physicalmentioning
confidence: 99%
“…The effect of the being bullied at school on workers’ mental health was, smaller than that for other factors, such as psychosocial work environment; however, school bullying may be a predisposing factor for psychological distress among workers. The higher levels of work engagement among people who experienced being bullied at school may be because some of them might have overcome the experience of being bullied to gain more psychological resilience [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, those who were bullied at school might be expected to have reduced levels of personal psychological resources such as self-efficacy, self-esteem, optimism, and a sense of coherence [ 11 ], which could result in reduced work engagement [ 31 , 32 ]. At the same time, other people who were bullied at school may have able to overcome the experience and gain more psychological resilience, as often has been observed in a population exposed to childhood maltreatment [ 29 ]. The finding may be explained by high work engagement reported by part of the sample who experienced posttraumatic growth after being bullied at school.…”
Section: Discussionmentioning
confidence: 99%